Analisis Pengaruh Platform Media Sosial terhadap Minat Berinvestasi Generasi Milenial di Pasar Modal (Studi Kasus pada Mahasiswa Jurusan Perbankan Syariah Angkatan 19 Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi) - Marselino, Nugi; Martilova, Novera (Lembaga Yasin AlSys, 2024)
The use of internet media and social media platforms among millennial students studying Sharia Banking at the Sjech M. Djamil Djambek State Islamic University Bukittinggi has grown rapidly. However, this generation’s interest in investing in the capital market is still lacking because their knowledge about this is limited. This research aims to determine the influence of social media platforms on the millennial generation’s interest in investing in the capital market. The research method used is quantitative, with data collection through observation and questionnaires. Data analysis techniques include correlation analysis, simple linear regression analysis, t test, and determinant test. The results show that there is a significant influence of social media platforms on the investment interest of the millennial generation in the capital market, with a strong correlation and a large contribution.